Potensi Na2SiO3 yang disintesis dari Batu Tuff sebagai bahan dasar Sintesis Silika Mesopori - Muhammad Iqbal Alzain; Syamsi Aini; Ridha Santika (Departemen Kimia FMIPA UNP, 2019)
Mesoporous silica was synthesized using sodium silicate obtained from tuff stones Indarung hills in Padang, Indonesia. Mesoporous silica was synthesized from sodium silicate and P104 as surfactant in acid condition. The result from characterization using spectrofottometer Fourier Transform Infrared (FTIR) are shown wavelength at 806 cm-1, 1058 cm-1, 1647 cm-1, and 3476 cm-1 that indicates mesoporous silica. FTIR data were strengthened using XRD with a wide and low diffractogram at 2θ=22°. The results show that tuff stones have potential to be used as a precrusor for synthesis mesoporous silica.